Lipopolysaccharide-induced CCN1 production enhances interleukin-6 secretion in bronchial epithelial cells - Shi, Lin (Cell Biol Toxicol, 2017)
Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is a clinical complication caused by primary or secondary lung injury, as well as by systemic inflammation. Researches regarding molecular pathophysiology of ALI/ARDS are immerging with an ultimate aim towards developing prognostic molecular biomarkers and molecule-based therapy. However, the molecular mechanisms concerning ALI/ARDS are still not completely understood. The purpose of the present study was to identify a crucial role of CCN1 in inflammatory microenvironment during ALI/ARDS and focus on a potential communication between CCN1 and interleukin-6 (IL-6) in the airway epithelial cells. Our data illustrated that the expression levels of CCN1 and IL-6 in bronchoalveolar lavage fluid (BALF) in a lipopolysaccharide (LPS)-induced ALI mouse model were significantly elevated and the pulmonary expression of CCN1 was restricted to bronchial epithelial cells. Interestingly, both endogenous and exogenous CCN1 stimulated IL-6 production in vitro. Furthermore, LPS-induced IL-6 production in a bronchial epithelial cell line was blocked by CCN siRNA whereas CCN1 induced by LPS was sensitive to PI3K inhibition. Together, our data indicate a linear signal pathway, LPS-CCN1-IL-6, existing in bronchial epithelial cells after LPS exposure. This finding may represent an additional mechanism and a novel target for development of therapy and biomarker on ALI/ARDS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10565-017-9401-1) contains supplementary material, which is available to authorized users.